O contraponto da República: Raimundo Nina Rodrigues e a loucura epidêmica de Canudos (1897) - Mastrantonio, Bruno De Oliveira [UNIFESP] (2019)
This research aims to analyze the actions of the maranhense physician Raimundo Nina Rodrigues (1962-1906) on Collective Psychology’s field, in view of their political and scientific intentions. Based on the methodological proposal of the British historian Quentin Skinner, we sought to understand the meanings of Nina Rodrigues' texts from the construction of links between the author, his work and the social, political and scientific context in which he was inserted. A witness to the abolition of slavery and the proclamation of the Republic, this physician built his career around the Faculty of Medicine of Bahia, surrounded by a network of relations with doctors and politicians of national projection, and was deeply concerned with the issues that involved the construction of the nation at the moment of transition from the monarchical regime to the republican. Often associated with his studies on the Afro-Brazilian population, in which racial´s assumptions are evident, Nina Rodrigues had his thesis marked by scientific racism. However, from the analysis of the articles that the doctor dedicated to the religious communities in Brazil, among them the case of Canudos, we note an attempt to relativize the influence of the racial factor as a trigger for pathologies, in explaining of the specificities' of mestizo population of the Brazil. Approaching the authors of the "social psychology", Gabriel Tarde and Gustave Le Bon, Nina Rodrigues took into account political and social factors to explain Canudos, although he did not completely abandon the importance of race in the outbreak of the disease that he believed to have reached the sertaneja population.